Analisis Penggunaan Media Grup Telegram dalam Layanan Akademik: Studi Kasus di Prodi Teknik Mesin Universitas Jember - Halimah, Siti; Arina Rubyasih; Koesanto, Stefani Made Ayu Artharini (Buana Komunikasi (Jurnal Penelitian dan Studi Ilmu Komunikasi), 2024)
During the COVID-19 outbreak, the Indonesian government implemented several policies to handle and prevent the spread of the disease. One of the policies launched is to shift face-to-face services in universities towards implementing online academic services. The Mechanical Engineering Study Program implements the Telegram group feature as a social media for academic service processes. This research aims to understand how communication patterns have changed during the pandemic and post-pandemic period in telegram group media use analyzed from the uses and gratifications theory in the Mechanical Engineering Study Program at Jember University. This research uses a qualitative descriptive research methodology. Research data was collected by observing Telegram groups, interviews, and distributing questionnaires to students using Telegram groups. The results of this research state that there has been a change in communication patterns during the COVID-19 pandemic using the telegram group media from previously being conducted face-to-face. After the pandemic passed, even though there was adaptation to changes in communication patterns, students had other choices in using media. Not every student felt that the telegram group media was effective based on their communication needs.